Dynamic output feedback L∞ control of switched affine systems: An event-triggered mechanism. (February 2023) - Xie, Hongzhen; Zong, Guangdeng; Yang, Dong; Chen, Yunjun; Shi, Kaibo
Abstract: This work focuses on the dynamic output feedback L ∞ control for switched affine systems with dwell time constraints. The presence of affine terms leads to the absence of a common equilibrium point and further makes it more difficult to design dynamic output feedback controllers and avoid the triggering Zeno behavior. To save resources and eliminate the effects of affine terms, first, an improved event-triggered condition with a constant and output information is provided. It is proved that the proposed triggering condition can prevent Zeno behavior from happening by obtaining a minimal inter-event interval. Then construct a novel dynamic output feedback switched affine controller, which skillfully adopts the mode-dependent average dwell time approach with Lyapunov stability theory to obtain a more rigorous and complete control strategy. It not only accommodates the unavailable state information and network transmission restrictions, but also achieves the practical stability of the closed-loop system while ensuring the L ∞ performance from external disturbance to the output. Finally, the efficiency of the proposed algorithm is illustrated by simulating the buck-boost DC–DC converter. Highlights: A new dynamic output feedback control algorithm for switched affine systems is set up. An improved ETM with a constant and output information is proposed. The limit on the set to which the switched equilibria belong has been removed. A less conservative stability result is derived via an MDADT approach.